Safety and Security Engineering V 2013
DOI: 10.2495/safe130721
|View full text |Cite
|
Sign up to set email alerts
|

Seismic behavior of a precast hollow core wall under biaxial lateral cyclic loading

Abstract: The seismic performance of two geometrically similar precast concrete hollow core walls are investigated experimentally under biaxial lateral cyclic loading. Two wall specimens are detailed with steel-armouring at their base-to-foundation interfaces including supplementary unbonded post-tensioned prestress, fuse-bars and mechanical energy dissipators. Wall 1, with a fixed location of bonded fusebars and unbonded tendons, is tested under various biaxial load paths including "4-leaf clover" and "double 4-leaf cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Precast concrete wall panels typically have weak planes because the panels are relatively thin, and so their design is a critical consideration in determining the strength, stability, and integrity of the building in which they are used. Specifically, the seismic behavior of a precast sandwich panel structure depends significantly on the connection between the wall panel system and the foundation [1][2][3][4]. However, current design codes do not address the seismic design of precast sandwich panel connections.…”
Section: Introductionmentioning
confidence: 99%
“…Precast concrete wall panels typically have weak planes because the panels are relatively thin, and so their design is a critical consideration in determining the strength, stability, and integrity of the building in which they are used. Specifically, the seismic behavior of a precast sandwich panel structure depends significantly on the connection between the wall panel system and the foundation [1][2][3][4]. However, current design codes do not address the seismic design of precast sandwich panel connections.…”
Section: Introductionmentioning
confidence: 99%
“…However, there exists fundamental question whether this structure could resist lateral forces in the event of earthquake or not. Previous study has shown that RC structure experienced brittle mode failure when tested under lateral cyclic loading using British Standard (BS 8110) [2,3]. Unlike the gravity load and the wind load, seismic force is generated by the dynamic movement of the structure as it vibrates.…”
Section: Introductionmentioning
confidence: 99%